What will work fighting climate change with renewable energy, not nuclear power - Shrader-Frechette, K. S. (Kristin Sharon) (New York : Oxford University Press, 2011)
'What Will Work' makes the case that energy efficiencies and renewable energy not nuclear fission or 'clean coal' are the most effective, cheapest, and equitable solutions to the pressing problem of climate change.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 18, 2012).
Includes bibliographical references and index.
Keywords: Climatic changes; Nuclear energy -- Environmental aspects; Radioactive pollution of the atmosphere; Renewable energy sources